Correction: Pyrido[1, 2-a]pyrimidinium ions – a novel bridgehead nitrogen heterocycles: synthesis, characterisation, and elucidation of DNA binding and cell imaging properties. Issue 4 (6th January 2016) - Manna, Susanta Kumar; Mandal, Arabinda; Mondal, Suresh Kumar; Adak, Arup Kr; Jana, Akash; Das, Somnath; Chattopadhyay, Sourav; Roy, Somenath; Ghorai, Shyamal Kr; Samanta, Shubhankar; Hossain, Maidul; Baidya, Mahiuddin
Abstract : Correction for 'Pyrido[1, 2- a ]pyrimidinium ions – a novel bridgehead nitrogen heterocycles: synthesis, characterisation, and elucidation of DNA binding and cell imaging properties' by Susanta Kumar Manna et al., Org. Biomol. Chem., 2015, 13, 8037–8047.